(untitled) (Revista Apotheke, 2024)
In this experience report, a feminist and art-educational perspective is adopted, according to bell hooks, Gerda Lerner and Ana Mae Barbosa, with a focus on childhood, following the principle of equity of feminist movements, presenting women artists, such as Eli Heil , Frida Kahlo, Georgia O’Keeffe, Yayoi Kusama, Tarsila do Amaral, Agnés Thurnauer, Larissa Abi-Zaid and Shamsia Hassani, through different approaches in art workshops, in the Casa Azul Project, an autonomous project, carried out between 2021.2 and 2023.1 , for children aged between 4 and 8 years old. By presenting different techniques, names and experiences, we expand children’s imagination about the presence of women in the history of art and humanity, in addition to encouraging girls to take a leading role in their creations, based on references with which they identify.